Endodontic Treatment of Bilateral Maxillary First Premolars with Three Roots Using CBCT: A Case Report - Sujatha Gopal; Gijo John; K. Pavan Kumar; Swarna Latha; Suma Latha; Sowmya Kallepalli (Case Reports in Dentistry)
One of the determining factors for the success of endodontic therapy is understanding the morphological anatomy of the tooth structure and its variants in relation to its template anatomy. The internal anatomy of maxillary first premolars is particularly complex due to their variation in number of roots and canal configuration. However, the bilateral presence of three roots in a maxillary first premolar is of rare occurrence. This case report describes the unusual anatomy bilaterally detected in maxillary first premolars using Cone-Beam Computed Tomography.